2017
DOI: 10.1016/j.biomaterials.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Bolstering cholesteryl ester hydrolysis in liver: A hepatocyte-targeting gene delivery strategy for potential alleviation of atherosclerosis

Abstract: Current atherosclerosis treatment strategies primarily focus on limiting further cholesteryl esters (CE) accumulation by reducing endogenous synthesis of cholesterol in the liver. No therapy is currently available to enhance the removal of CE, a crucial step to reduce the burden of the existing disease. Given a central role of hepatic cholesteryl ester hydrolase (CEH) in intrahepatic hydrolysis of CE and subsequent removal of the resulting free cholesterol, in this work, we applied galactose-functionalized pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…13,14 Intracellular CE accumulation in macrophages can be reduced by enhancing the removal of unesterified or free cholesterol (FC), a process rate-limited by intracellular CE hydro-lysis catalyzed by neutral CE hydrolase (CEH), 15,16 and earlier studies from our laboratory have demonstrated CEH overexpression-mediated increase in CE mobilization. 1719 FC generated by CEH-mediated hydrolysis of CE becomes available for ApoA1 or High density lipoprotein-dependent efflux through FC transporters ABCA1/G1 20 and carried to the liver for final elimination from the body. Although overexpression of ABCA1 attenuates atherosclerosis, 21,22 deficiency of ABCA1 in macrophages enhances plaque progression.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Intracellular CE accumulation in macrophages can be reduced by enhancing the removal of unesterified or free cholesterol (FC), a process rate-limited by intracellular CE hydro-lysis catalyzed by neutral CE hydrolase (CEH), 15,16 and earlier studies from our laboratory have demonstrated CEH overexpression-mediated increase in CE mobilization. 1719 FC generated by CEH-mediated hydrolysis of CE becomes available for ApoA1 or High density lipoprotein-dependent efflux through FC transporters ABCA1/G1 20 and carried to the liver for final elimination from the body. Although overexpression of ABCA1 attenuates atherosclerosis, 21,22 deficiency of ABCA1 in macrophages enhances plaque progression.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the colloid stability in physiological conditions, the lifetime in blood circulation should be increased, and toxicity in vivo should be reduced; magnetite NPs are often coated or modified with biocompatible polymer molecules such as dextran and polyvinyl alcohol [9,11,12]. In this study, we used PEG-PEI to modify SPIO NPs, as it provides good solubility in aqueous solvents and prolongs circulation time in the bloodstream [20,32]. The TEM image indicated that profilin-1-labeled NPs displayed mono-dispersion, uniform size (average size ¼ 15-20 nm in the dry state) and spherical morphology (Figure 2(a)).…”
Section: Characterization Of Pfn1-cd-mnpsmentioning
confidence: 99%
“…Currently, several clinic drugs are available that slow the progression of atherosclerosis by lowering plasma lipid levels [19,20]. However, the equally important contribution of inflammation to the development of cardiovascular disease is overlooked by current therapies [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol plays an important role in cell membrane fluidity by being able to both cause membrane stability and by decreasing flexibility of nearby unsaturated acyl chains in membranes. Cholesterol also helps to maintain fluidity through inhibition of acyl-chain packing of cellular membranes (92). …”
Section: The Roles Of Various Lipid Classes In Disease Pathophysiologiesmentioning
confidence: 99%
“…This pre-clinical work by Hongliang He and coworkers demonstrated a promising treatment for alleviating the accumulation of cholesterol esters in patients suffering from atherosclerosis. (92)…”
Section: The Roles Of Various Lipid Classes In Disease Pathophysiologiesmentioning
confidence: 99%